Effects of Glyphosate Applied at Different Times on Dormant Zoysiagrass Cultivars in the Transition Zone - Dani McFadden; Jack D. Fry (Kansas Agricultural Experiment Station Research Reports, 2023)
Winter annual weeds become a major problem during winter dormancy in warm-season turfgrass stands. In the transition zone, a winter glyphosate application is a common practice to reduce winter annual weed competition in zoysiagrass before emerging from dormancy in the spring. Research was conducted on the effects of glyphosate application timings on spring greenup and quality of experimental zoysiagrass genotypes compared to commercially available cultivars. Preliminary data from this study revealed a quicker spring greenup when glyphosate was applied in November compared to March. However, March-applied glyphosate significantly reduced cool-season weeds in experimental plots and enhanced quality compared to the nontreated control.
Keywords: winter annuals; weed control